A Different Kind of Kid, A Different Kind of Teacher Education: Middle Grades Teachers Reflect on Their Preparation to Teach Young Adolescents - Moses K Ochanji; Rong-Ji Chen; Erika Daniels; Marlene L Deringer; Janet McDaniel; Laurie Stowell; Christina Cambra-Adamson (Middle Grades Review, 2016)
Good teaching at the middle grades comes out of a deep understanding of the unique cognitive, physical, social, emotional, and moral needs of young adolescents. Therefore specialized preparation is necessary to help teacher candidates understand how to operationalize the intersection of young adolescent development and the effective pedagogy that addresses their needs. This paper focuses on a qualitative study of experienced middle school teachers who graduated from a middle level preparation program or an elementary or secondary preparation program in terms of how well prepared they felt and feel to meet the widely varied needs of young adolescents. Confidence in preparation leads to high self-efficacy, which is important for perseverance and effectiveness. Graduates of a middle level preparation program reported higher levels of confidence in their preparation to teach young adolescents.
Keywords: Middle level education; Teacher preparation; Teacher voice